Intersectional Feminism and Social Justice in Teen Vogue. Issue 3 (1st December 2021) - Crookston, Shara; Klonowski, Monica
Abstract: In this article, we argue that Teen Vogue has evolved to encompass aspects of intersectional, feminist activism that is particularly evident in the 2017 "Voices" section of the magazine. This evolution challenges previous research that has found that, historically, teen magazines focus heavily on heteronormativity, ideals of beauty, and consumerism. Our analysis of the content of this section of Teen Vogue in 2017 demonstrates that teen magazines can be reimagined as legitimate sources of intersectional activist feminist information for readers. Despite these positive changes, however, Teen Vogue continues to advertise clothing brands that many adolescent girl readers are likely unable to afford, thereby reinforcing superficial postfeminist notions of empowerment.